2001
DOI: 10.1348/000711201161118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dissociation at encoding on intrusive memories for a stressful film

Abstract: The occurrence of memory intrusions after a trauma has been linked to peri-traumatic dissociation. In this study, we attempted to induce dissociation experimentally and investigate the impact on intrusive memories. A total of 39 undergraduates were randomly assigned to watch a stressful film under standard conditions or under a dual-task condition in which they simultaneously performed a tapping task. They rated their distress post-film and again after 2 weeks, and kept a diary of intrusive memories. Contrary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 0 publications
7
84
0
Order By: Relevance
“…Our results are also in line with those of Brewin and Saunders (2001), who found that artificially inducing dissociation by means of a dual task during exposure to a video fragment does not lead to deterioration of recall performance. However, while these two previous studies clearly show that dissociation is unrelated to recall performance in terms of hits, both failed to look at commission errors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are also in line with those of Brewin and Saunders (2001), who found that artificially inducing dissociation by means of a dual task during exposure to a video fragment does not lead to deterioration of recall performance. However, while these two previous studies clearly show that dissociation is unrelated to recall performance in terms of hits, both failed to look at commission errors.…”
Section: Discussionsupporting
confidence: 92%
“…One possibility is that this association has to do with high dissociators suffering from limited working memory capacity. A limited working memory capacity might hamper encoding, leading to gaps in memory (Brewin and Saunders, 2001), which are later filled in by participants, thereby leading to confabulations. Thus, the first issue examined in the current study is whether high dissociators' commission errors are related to working memory problems.…”
Section: Introductionmentioning
confidence: 99%
“…Diary Participants in the diary group were asked to use an A5-format diary to record any intrusions of the films during the four days following the film (e.g., Brewin & Saunders 2001;Davies & Clark 1998;Holmes et al 2004). They noted each intrusion's content ("Describe the content of your intrusion.")…”
Section: Methodsmentioning
confidence: 99%
“…The stressful film paradigm creates an analogue situation in which response to trauma can be investigated in a controlled way (Holmes et al 2004). A number of studies investigating information processing abnormalities have used this method to study the development of intrusive memories in the days after watching a highly stressful film (Brewin & Saunders 2001;Davies & Clark 1998;Holmes et al 2004;Stuart et al 2006). In most of these studies, participants were presented with a diary for the online registration of the frequency and characteristics of their intrusions rather than via an unexpected presentation of retrospective self-report questionnaires at a follow up session.…”
mentioning
confidence: 99%
“…The dual representation theory (Brewin, Dalgleish, & Joseph, 1996) states that intrusion development depends on the balance between peri-traumatic visuospatial and verbalconceptual processing. During extreme stress, information processing shifts towards more visuospatial processing, resulting in image-based trauma representations that are prone to automatic intrusive activation (Holmes & Bourne, 2008).Experimental studies show that performing a visuospatial task (e.g., complex pattern tapping) during the encoding of an aversive film reduces subsequent intrusion frequency (Brewin & Saunders, 2001;Holmes, Brewin & Hennessy, 2004;Stuart, Holmes & Brewin, 2006). However, movement per se is confounded with the visuospatial aspect in these studies.…”
mentioning
confidence: 86%